The Efficient Role of Aquatic Plant (Water Hyacinth) in Treating Domestic Wastewater in Continuous System - Shahabaldin, Rezania; Mohd Fadhil, Md Din; Shazwin, Mat Taib; Farrah Aini, Dahalan; Ahmad Rahman, Songip; Singh, Lakhveer; Hesam, Kamyab (Taylor and Francis, 2015)
In this study, Water Hyacinth (Eichhornia crassipes) was used to treat domestic wastewater. Ten organic and inorganic parameters were monitored in three weeks for water purification. The six chemical, biological and physical parameters included Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (NH3-N), Total Suspended Solids (TSS) and pH were compared with the Interim National Water Quality Standards, Malaysia River class ification (INWQS) and Water Quality Index (WQI). Between 38% to 96% of reduction was observed and water quality has been improved from class III and IV to class II. Analyses for Electricity Conductivity (EC), Salinity, Total Dissolved Solids (TDS) and Ammonium (NH4) were also investigated. In all parameters, removal efficiency was in range of 13-17th day (optimum 14th day) which was higher than 3 weeks except DO. It reveals the optimum growth rate of water hyacinth has great effect on waste water purification efficiency in continuous system and nutrient removal was successfully achieved.